1996
DOI: 10.3354/meps141027
|View full text |Cite
|
Sign up to set email alerts
|

Delayed metamorphosis in Florida hermit crabs: multiple cues and constraints (Crustacea: Decapoda: Paguridae and Diogenidae)

Abstract: 1 examined the effects of food availablllty, shell availability and the presence of adults on survlval and duration of the megalopal stage of the lntertldal h e r m~t crabs Pagurus maclaughlinae Garcla-Gomez, Paguristes tortugae Schmitt and Cllhananus vlttatus (Bosc) In the laboratory. I also cons~dei-ed the role of substrate avdilability on C. vlttatus. All species delayed metamorphosis significantly in the absence of empty shells; shells also enhanced megalopal survival In P, maclaughlinae and C. vittatus. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…The paucity of evidence for demersal fishes contrasts with an extensive body of invertebrate literature, for which delays in settlement are well documented and experimentally examined (e.g. Richmond 1985, Lipcius et al 1990, Pechenik 1990, Pechenik et al 1993, Davis 1994, Harvey 1996, Stoner et al 1996. The present study is the first to experimentally examine in the field the capacity of a fish species to delay metamorphosis.…”
Section: Introductionmentioning
confidence: 71%
“…The paucity of evidence for demersal fishes contrasts with an extensive body of invertebrate literature, for which delays in settlement are well documented and experimentally examined (e.g. Richmond 1985, Lipcius et al 1990, Pechenik 1990, Pechenik et al 1993, Davis 1994, Harvey 1996, Stoner et al 1996. The present study is the first to experimentally examine in the field the capacity of a fish species to delay metamorphosis.…”
Section: Introductionmentioning
confidence: 71%
“…Substances released by conspecifics should be relevant stimuli indicating an adequate habitat (Jensen, 1989). Also, low salinity and estuarine vegetation (Wolcott and De Vries, 1994;Forward et al, 1994Forward et al, , 1996, or substratumrelated cues (Christy, 1989;Harvey, 1996;Weber and Epifanio, 1996) have been identified as effective cues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments by Weber and Epifanio (1996) showed that stimuli related to the preferred adult substrata, as well as the presence of adult conspecifics, can induce metamorphosis in competent megalopae of Panopeus herbstii. Also, Harvey (1996) demonstrated that the time to metamorphosis was affected in two hermit crabs, Pagurus maclaughlinae and Paguristes tortugae, by exposure to adultconditioned water and in another hermit crab, Clibanarius vittatus, by the presence of sediment.…”
Section: Introductionmentioning
confidence: 99%
“…The main methodological difference between the present study and that of Rodrigues and Hebling (1989) was the presence of the mangrove sediment within the experimental container. The physicochemical characteristics of the substrates might strongly modulate the decapod metamorphosis, such as temperature (Jamieson and Phillips, 1993;McMillan et al, 1995;Anger et al, 2004), salinity (Islam et al, 2005), and conspecific chemical cues (Harvey, 1996;O'Connor and Judge, 1997;Gebauer et al, 1998;Rodríguez and Epifanio, 2000;Gebauer et al, 2002). Future studies, addressing specifically this issue, could provide important information to accelerate the larval development of U. cordatus and to optimize their larviculture.…”
Section: Discussionmentioning
confidence: 99%